From public action to public administration: where does it lead? - Radin, Beryl; Cooper, Terry (1997)
Minnowbrook I and Minnowbrook II differ in one important way. Minnowbrook I involved mostly scholars who came to the field primarily through formal academic training. Several of those who participated in Minnowbrook II are products of community-based applied revisions of so-called new public administration in the 1960s. Radin served as a union employee and then a staff member of the U.S. Commission on Civil Rights. Cooper worked as a minister at several inner-city churches. Both Radin and Cooper took their doctorates later in their careers, after extensive street level experience. From this perspective they focus on the unique political setting of public administration, on the field's publicness, on the alience of theories of change, on a process perspective, and on "soft" research methodologies. - Reproduced
Keywords: Public administration - United States; Public administration